Economic openness, external financing and sustained growth - Maia, José Luis; Ortiz, Javier (Estudios de Economía, 2016)
In this paper we make explicit the relationship that exists between a set of structural reforms –as those undertaken in Argentina at the beginnings of the nineties- and the growth process that they generate. It is argued that such reforms, and particularly those related to the external sector, improve the efficiency in resource allocation and hence bring about an increase in the marginal productivity of the existing per capita capital stock. This improvement in efficiency puts the economy on a growth path having either temporary or permanent characteristics. In this model, as in other intertemporal paradigms of open economies with optimizing agents, the country resorts to the international credit market in order to finance higher consumption and investment levels. The paper also offers empirical evidence on a set of countries which implemented reforms deemed to be successful in terms of the evolution of the key economic variables, that is, the rate of per capita gross domestic product, the gross investment to product ratio, and the product to capital incremental ratio (as an approximation to the marginal productivity of capital). Additionally, we trace the changes in the openness coefficient as an indicator of the scope of one of the reforms that attend successful structural changes. Based on the results obtained from the model and the international empirical evidence, it is recommended to deepen the overall policy of structural reforms –of which external openness is a part- in order to generate a sustained growth process.